International Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
This article provides an overview of several challenges that involve Bitcoin and other cryptocurrencies. After briefly discussing the underlying technology, it discusses challenges related to cryptocurrencies that regulators face at this point in time. This includes issues regarding Initial Coin Offerings and cryptocurrencies in general, as well as cryptocurrencies as an investment instrument. It also includes an analysis of cryptocurrencies compared to the real economy. The article concludes that scholars are not unanimous regarding the regulation of Bitcoin and cryptocurrencies, and that cryptocurrencies, at least up till now, do no follow trends of the real economy.